Cultural Heritage Tour Package Planning For Salt Education In Kusamba, Dawan District, Klungkung Regency - Selamet, I Wayan Agus; Satia Negara, I Made Weda; Elisa Yonce, Atabuy Frit; Permadi, Komang Satya; Sudana, I Made (Politeknik Internasional Bali, 2025)
This study aims is cultural heritage tour package planning for salt education in Kusamba, Dawan District, Klungkung Regency. The salt-making traditionan important form of intangible cultural heritage is experiencing decline due to low economic returns and shifting livelihood preferences among local residents. Recognizing its cultural value and tourism potential, this study aims to design an educational tourism package that can support cultural preservation and local empowerment. A qualitative research approach with a phenomenological and content analysis design was employed. Data were collected through field observations, in-depth interviews, and documentation involving salt farmers, community leaders, and tourism stakeholders. Data analysis followed the Miles and Huberman interactive model and was strengthened through triangulation and member checking. The findings reveal that Kusamba’s traditional salt production process provides strong experiential and educational value. Based on these findings, a one-day itinerary titled Cultural Heritage Salt Education Tour Kusamba was formulated. Marketing strategies are carried out through offline collaboration with travel agencies and brochure distribution, as well as online promotion via websites, social media, and online travel agents. TripAdvisor reviews indicate high appreciation for the authenticity and educational aspects of the experience. This research contributes a structured model for transforming declining traditional livelihoods into sustainable heritage-based educational tourism. The novelty lies in positioning salt education tourism as a replicable approach for community-based cultural revitalization in rural Indonesia.